2021
DOI: 10.1177/20552173211017159
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 vaccination willingness among people with multiple sclerosis

Abstract: Background Hesitancy to receive COVID-19 vaccination is a major public health concern. COVID-19 vaccine willingness and the factors contributing to willingness in adults with multiple sclerosis (MS) is unknown. We administered an online survey from 1 December 2020 to 7 January 2021 to adults with MS to estimate COVID-19 vaccine willingness among adults with MS. Bivariate analysis with chi-square testing compared categorical variables associated with vaccine willingness. Results Of 401 respondents, 70.1% were w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
41
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 18 publications
(38 reference statements)
2
41
0
Order By: Relevance
“…17 However, ∼6% of American PwMS are unwilling to receive the SARS-CoV-2 vaccine, and >20% of PwMS are vaccine hesitant. 6 , 7 Frequent concerns for vaccine hesitant PwMS were vaccine safety and efficacy and potential short- and long-term side effects. 6 , 8 In addition, most vaccine hesitant PwMS expressed the desire for additional information.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…17 However, ∼6% of American PwMS are unwilling to receive the SARS-CoV-2 vaccine, and >20% of PwMS are vaccine hesitant. 6 , 7 Frequent concerns for vaccine hesitant PwMS were vaccine safety and efficacy and potential short- and long-term side effects. 6 , 8 In addition, most vaccine hesitant PwMS expressed the desire for additional information.…”
Section: Discussionmentioning
confidence: 99%
“… 6 , 7 Frequent concerns for vaccine hesitant PwMS were vaccine safety and efficacy and potential short- and long-term side effects. 6 , 8 In addition, most vaccine hesitant PwMS expressed the desire for additional information. 8 Unfortunately, no safety data pertaining specifically to PwMS have been reported from the various SARS-CoV-2 vaccine trials, and extrapolation of the safety data from the general population to PwMS is unclear, largely due to the uncertain impact of DMTs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, the current epidemiological situation related to COVID-19 may have a significant sociopsychological influence on vaccination's acceptance among people whether having certain diseases or not. Indeed, recent studies describing COVID-19 vaccination's willingness in patients with MS [20][21][22] reported that almost 60-80% of interviewed MS participants were willing to receive a COVID-19 vaccine. As authors reported, vaccine willingness was statistically significant associated with increased perceived personal risk of COVID-19, prior influenza vaccine acceptance, higher educational level, older age, and discussion of the importance of COVID-19 vaccine with neurologists.…”
Section: Discussionmentioning
confidence: 99%